Life Cycle Assessment of Indonesian Traditional Food: A Case Study of Lumpia Semarang - Yosef Barita Sar Manik; Brilian Maulani Putri; Arifah Arsanti; Alexandra Paloma Sarmento (University of Sultan Ageng Tirtayasa, 2025)
The production process of traditional food in small industries can have significant environmental impacts due to energy consumption, agricultural inputs, and emissions generated during production. This research aims to analyze the life cycle of Lumpia Semarang production using a functional unit of 10 portions of Lumpia, where each portion consists of 3 pieces. The gate-to-gate approach was applied using OpenLCA software with the CML-IA Baseline method, ReCiPe Midpoint 2016 (H), and IPCC method, following ISO 14040 and 14044 standards. The results show that producing 10 portions of Lumpia contributes to a global warming potential (GWP100a) of 6.12E+00 kg CO₂ eq, ozone layer depletion of 3.72E-07 kg CFC-11 eq, human toxicity of 1.74E+00 kg 1.4-DB eq, acidification of 5.11E-02 kg SO₂ eq, and eutrophication of 2.56E-02 kg PO₄ eq. The hotspot analysis indicates that the main environmental burdens originate from the raw material production stage, particularly agricultural and livestock inputs (palm fruit bunch, broiler, maize, wheat, and soybean), as well as PET plastic packaging. The frying process also contributes notably to global warming potential due to LPG gas and palm oil consumption, while producing used cooking oil that poses waste management challenges.These findings highlight the need for sustainable improvements in Lumpia production, particularly in resource efficiency, waste management, and the use of eco-friendly packaging to reduce overall environmental impacts. Implementing sustainable sourcing practices, optimizing energy use, and introducing biodegradable packaging alternatives can help minimize the environmental footprint of Lumpia while maintaining its economic and cultural significance.